Implementasi Istishab Sebagai Perkembangan Hukum Islam - Ihza, Ahmad; Nurlaeli, Ida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The dimension of Islamic law can be achieved by emphasizing the theory of benefit as the main consideration for determining a law. One of them is an effort to review istishab as an argument for determining the law, namely by determining the status of the origin. Sometimes the origin is permissible, free from demands, and sometimes it is permanent. Istishab is a method of ijtihad. Ijtihad is the inner dynamic for the birth of change to maintain the comprehensiveness of Islamic law. Istishab itself is a source of law that is debated by scholars and whether istishab itself is included as a proof or not. The first opinion says hujjah as a legal determination, the second istishab is not used as a proof in making law, the third is a proof in determining new problems. Istishab is also widely applied in various cases, both in the fields of family law, criminal, civil and economic law. More than that, the important value of the application of istishab is the principle of law in Indonesia (the principle of presumption of innocence), the principle of legality and the principle of Nullum delictum nulapoena sine praevia leg poenali makes it important to be studied further.